Causes, Benefits, and Risks of Business Tax Incentives - Klemm, Alexander (IMF Working Papers; Working Paper ;, 2009)
This paper provides an updated overview of tax incentives for business investment. It begins by noting that tax competition is likely to be a major force driving countries' tax reforms, and discusses tax incentives as a possible response to this. This is complemented by other arguments for and against tax incentives, and by an illustrative analysis of different incentives using effective tax rates. Findings from the empirical literature on tax incentives are also presented. Based on the overview of theoretical and empirical findings, the paper then suggests a matrix of criteria to determine the usefulness of different tax incentives depending on a country's circumstances.